A experiência de mulheres profissionais do sexo vivendo com HIV - Leite, Thaisa da Conceição Ramos (2018)
This dissertation proposes to analyze the experience of female sex workers living with HIV. There are still few studies that explore the experiences and needs of this population, seeking to understand their meanings within their social context. From this perspective, the research seeks to understand the meanings, to the sex worker about the changes in her life after discovering that she would have to live with HIV; the difficulties encountered, the attitudes, the social conditions and the interactive processes, as well as their future perspectives. In order to carry out the research, the qualitative approach is used with the technique of semi-structured interviews, observation and field diary, with the intention of capturing not only perceptible actions to the eyes, but the interviewees' perception about their experience of with HIV. The data are submitted to thematic analysis. The search for these women occurred in the specific care places for people who take the retroviral treatment, more specifically in the Specialized Care Service (SAE) of one county of the Baixada Cuiabana and another from west region of Mato Grosso State. The interviewees are black and low-income women living in neighborhoods far from the city center, there are difficulties in accessing the health service due to the distance traveled to the SAE. In addition, stigma is present in all walks of life of these women. They avoid revealing their status as seropositive, and claim to have conducted programs without the use of condoms, even after a positive HIV diagnosis. This information is relevant to the health service, health staff, and researchers working directly with this population, since understanding the way of life and the experience of living with HIV can help in planning the actions and strategies of inclusion of this group in the health services, as well as in the expansion of the dialogue on intersectionality, HIV / AIDS and stigma.